2011
DOI: 10.4081/dts.2011.e7
|View full text |Cite
|
Sign up to set email alerts
|

Depletion of drug-surviving glioma cells by a second phase treatment with low concentration of salinomycin

Abstract: Standard treatment for glioma includes surgery, radiotherapy and chemotherapy but the outcome of patients is very poor. Antineoplastic drugs are usually administered alone or in combination for variable times (continuously or in cycles) in a single phase schedule. In this study we explored in vitro the antiproliferative effect of a 2 phases treatment. In the first phase, glioma cells where treated for 3-4 weeks with hydroxyurea (HU) or aphidicolin and then for 4 weeks with salinomycin, a drug that preferential… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 25 publications
0
9
0
Order By: Relevance
“…However, toxicity may be the main concern. For instance, SAL is very toxic to other normal cells at concentrations effective against cancer stem-like cells [ 166 ] and therefore it is unlikely that this drug will be useful as single agent [ 167 ]. The ability of NIG to induce apoptosis or necrosis by increase K + efflux occurs only at relatively high concentration (2.5–7.5 µM) [ 6 ] that may be not tolerated in vivo.…”
Section: Ionophores In Ongoing Clinical Trials For Cancer Treatmenmentioning
confidence: 99%
“…However, toxicity may be the main concern. For instance, SAL is very toxic to other normal cells at concentrations effective against cancer stem-like cells [ 166 ] and therefore it is unlikely that this drug will be useful as single agent [ 167 ]. The ability of NIG to induce apoptosis or necrosis by increase K + efflux occurs only at relatively high concentration (2.5–7.5 µM) [ 6 ] that may be not tolerated in vivo.…”
Section: Ionophores In Ongoing Clinical Trials For Cancer Treatmenmentioning
confidence: 99%
“…After the discovery of salinomycin as an anti‐cancer agent and the suggestion that it has a 100‐fold greater pharmacological effect on cancer stem cells than paclitaxel, several in vitro and in vivo studies have been carried out to evaluate the effects of salinomycin on various cell lines, including cancer and cancer stem cells . In terms of brain tumor therapy, only few studies have shown the effects of salinomycin on glioblastoma cells . Delwar et al reported that tumor cells (glioma DBTRG‐05MG cell line) surviving to hydroxyurea or aphidicolin are slowly depleted by treatment with salinomycin .…”
Section: Introductionmentioning
confidence: 99%
“…In terms of brain tumor therapy, only few studies have shown the effects of salinomycin on glioblastoma cells . Delwar et al reported that tumor cells (glioma DBTRG‐05MG cell line) surviving to hydroxyurea or aphidicolin are slowly depleted by treatment with salinomycin . Calzolari et al investigated the effects of tumor necrosis factor‐related apoptosis‐inducing ligand (TRAIL), salinomycin and the combination of both agents in glioblastoma cell lines and demonstrated that salinomycin enhanced TRAIL‐induced apoptosis, mainly by upregulating the expression of TRAIL‐R2 .…”
Section: Introductionmentioning
confidence: 99%
“…The effects of salinomycin on brain tumor cells do not have been explored. In this context, a recent study, using the glioma DBTRG-05MG cell line, showed that tumor cells surviving to hydroxyurea or aphidicolin are slowly depleted by treatment with salinomycin [18] .…”
Section: Introductionmentioning
confidence: 99%